ANALYSIS OF READING LITERACY CULTURE OF ELEMENTARY SCHOOL STUDENTS IN WORI DISTRICT - Elfin Lahiang; Mayske R Liando; Richard D Pangkey (RADJA PUBLIKA, 2026)
This study aims to analyze the reading literacy culture of students at GMIM Kulu Elementary School, Wori District, North Minahasa Regency. This research is motivated by the low reading habits of students and the suboptimal implementation of literacy programs in schools. Therefore, this study focuses on three main issues: students' reading literacy culture, factors influencing it, and the role of teachers and the school environment in building a reading literacy culture. This research employed a qualitative research method with a phenomenological or case study approach. The research subjects consisted of the principal, teachers, and students of GMIM Kulu Elementary School. Data collection techniques included observation, interviews, and documentation. Data analysis employed the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. Data validity was verified through source triangulation, technical triangulation, and member checking. The results of the study indicate that students' reading literacy culture at GMIM Kulu Elementary School still needs improvement. Students' reading habits are still low, and reading activities have not yet become a routine habit. Factors influencing reading literacy culture include internal factors such as students' interest and motivation to read, as well as external factors such as family environment, school environment, and the availability of literacy facilities. Furthermore, teachers play a significant role in literacy activities, particularly in guiding and motivating students to read. However, limited literacy facilities at school remain a barrier to developing students' reading literacy culture. Based on the results of this study, more targeted efforts are needed from schools, teachers, and parents to improve students' reading literacy culture by providing adequate literacy facilities and implementing more structured literacy programs.